Prevalence of illness, poor mental health and sleep quality and low energy availability prior to the 2016 Summer Olympic Games - Drew, M.; Vlahovich, N.; Hughes, D.; Appaneal, R.; Burke, L. M.; Lundy, B.; Rogers, M.; Toomey, M.; Watts, D.; Lovell, G.; Praet, S.; Halson, S. L.; et al. (British Journal of Sports Medicine, 2018)
Objective: Establish the prevalence of illness symptoms, poor sleep quality, poor mental health symptoms, low energy availability and stress-recovery state in an Olympic cohort late in the 3?months prior to the Summer Olympic Games.